MANAJEMEN SEKOLAH DALAM PENERIMAAN SISWA BARU TERHADAP KESIAPAN GURU DALAM MENDIDIK DI SD LEMBAH BINUBU - Zunaidi M Rasid Harahap; Wantini Wantini (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to describe and analyze school management in the acceptance of new students to the readiness of teachers to educate in SD binubu valley. This research method is qualitative type of phenomenology. The researc h setting was Lembah Binubu Elementary School, the subject of this study was the principal. Data collection techniques through observation, interviews, and documentation. Interviews were conducted with the school principal, observations were carried out by school environment participants regarding student acceptance of teacher readiness in teaching, as well as documentation. The results showed that the admission of new students still used the manual method due to inadequate facilities and the community was still intrigued (technologically failed). So that making changes requires a long time. Then the teacher is always guided by the school principal in the preparation of new teachings, so that the teacher's readiness in learning in class runs smoothly. However, seeing from this situation, the government needs to pay attention to the existing schools in rural areas, both the infrastructure of teacher training for schools in rural areas can be equivalent to schools in urban areas.